تقييم مستوى استراتيجيات التكيف للتعامل مع الضغوط لدى أمهات أطفال التوحد في اللاذقية - Dona, Esa; Sebih, Safaa; reslan, Sabah (Latakia University Journal -Medical Sciences Series, 2019)
تقييم مستوى استراتيجيات التكيف للتعامل مع الضغوط لدى أمهات أطفال التوحد في اللاذقية عيسى دونا صفاء صبح صباح رسلان إن العناية بأطفال ذوي الاحتياج الخاص ( التوحد) تعد أكثر صعوبة لذلك فان الأسرة تستخدم استراتيجيات تكيُف تبتدعها من ذاتها لتستطيع تحمل مسؤولية وأعباء الطفل المعاق . الهدف: هدفت هذه الدراسة إلى الكشف عن مستوى إدارة استراتيجيات التكيف للضغوط لدى أمهات أطفال التوحد وعلاقتها ببعض المتغيرات.....أدوات البحث وطرائقه: أجريت هذه الدراسة على عينة مؤلفة من (34) أما" من أمهات الأطفال التوحديين تم اختيارهم من جمعية التوحد ومركز بشائر النور في محافظة اللاذقية بطريقة عشوائية.جمعت البيانات باستخدام استمارة تتضمن البيانات الشخصية واستمارة تتضمن مقياس إستراتيجيات التكيف النفسية الخاص بأمهات الأطفال التوحديين والمؤلف من (64) فقرة موزعة على سبعة أبعاد... النتائج : خلصت النتائج إلى أن مستوى إدارة استراتيجيات التكيف لأمهات الأطفال التوحديين في جميع مجالات المقياس كان مستوى متوسط , وكان مستوى مرتفع في البعد الدين كما أظهرت نتائج الدراسة وجود فروق ذات دلالة إحصائية لمتغيرات جنس طفل التوحد والمستوى التعليمي للأم وشدة حالة الطفل في مستوى استراتيجيات التكيف لدى أمهات الأطفال التوحديين وعدم وجود فروق ذات دلالة إحصائية لمتغير المـستوى الاقتـصادي للأسرة . وأوصت الدراسة بضرورة بناء برامج تدريبية على استراتيجيات تستخدمها الأمهات في التعامل مع الضغط الناتج عن وجود الطفل التوحدي . The careful of autism children is very difficult so the family uses coping strategies creative from herself for hold responsibility of autism children .Objectives: This study aimed to detect the coping strategies for mothers of autism children and relation it with some variables. Material and method: This study was conducted on a sample of (34) mothers of autism Children’s were selected randomly, from the center of autism and Bashaer Alnour in the latakia. The data were collected using a questionnaire containing personal data and the researcher used a scale of Coping strategies for mothers of autism children’s which it consists of (64) items distributed on seven dimensions Results: the level of Coping management strategies for mothers of autism children’s in all areas of the scale was middle level but it was high only in the religious strategy . The results of the study showed there is no statistically significant differences at the level of Coping management strategies to the variable of economic level of households. but there was statistically significant differences at the level of Coping management strategies to the variables of gender of the children , educational level of the mother and the severity of case .the researcher recommends it necessary to but training educational about coping strategies that used by mothers on how to deal with stress that is result from autism children’s .